KOMUNIKASI ORGANISASI, POLA KARIR, MOTIVASI BERPRESTASI, KOMITMEN ORGANISASI DAN KINERJA PEGAWAI - I Komang Sugianta (Universitas Pendidikan Nasional, 2015)
aims to determine the effect of Organizational Communication, CareerPatterns, Achievement Motivation and Organizational Commitment on Employee PerformanceThe respondents of this study is the staff amounting to 121 people of Cooperatives,SMEs, Trade and Industry Departement at Klungkung regency,. The data analysis is thestatistical method of Structural Equation Modeling (SEM) with AMOS software version 20.0,The analysis showed that: Achievement Motivation has a direct influence in a positiveand significant impact on Organizational Commitment, while Organizational CommunicationandCareer Patterns have a direct influence in a positive unsignificant to OrganizationalCommitment. Achievement Motivation and Organizational Commitment has a direct influencepositively and significantly on employee performance, while the OrganizationalCommunication and Career Patterns have a direct influence in a positive unsignificant toEmployee PerformanceKeywords : Communication Organization, Career pattern, Achievement Motivation,Organizational commitment and employee performance.